Antonyms in the Qur'an According to the Perspective of Ali Al-Khuli - Taufiq, Mirwan Akhmad; Ilmiyah, Zahrotul; Husna, Siska Syifa'ul (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This study aims to identify the antonyms present in Surah Al-Waqiah. It provides a general description of antonyms (al-Tadhad), the theory used in determining antonyms (al-Tadhad), and the classification of antonym types (al-Tadhad) found in Surah Al-Waqi'ah based on the perspective of M. Ali Al-Kuli. The study adopts a library research approach, using the primary data of Surah Al-Waqi'ah from the Quran and secondary data from books and articles on semantics and antonyms. Data analysis follows the Miles and Huberman technique, involving data collection, reduction, presentation, and conclusion. The findings reveal six types of antonyms: mutadarrij antonyms (multilevel), juz'I antonyms (sections), imtidadiy antonyms (extensional or straight line), had (binary) antonyms, intisabiy (affinity) antonyms, and axis (poles) antonyms. However, from M. Ali Al-Khuli's perspective, Surah Al-Waqi'ah does not contain the antonyms of Antonim Amudi, Antonim Daairi, and Antonim Rotiby. The practical implication of this study is that every word in the Quran holds its aesthetic meaning.